Microalgae Bioenergy with Carbon Capture and Storage (BECCS): An emerging sustainable bioprocess for reduced CO2 emission and biofuel production. (September 2019) - Choi, Yoon Young; Patel, Anil Kumar; Hong, Min Eui; Chang, Won Seok; Sim, Sang Jun
Abstract: CO2 is main contributor of global warming crisis. Among various existing carbon-capture technologies, microalgae based biological carbon-capture is one of the promising less energy consuming technology. Microalgae are gaining attention for bridging carbon mitigation and bioenergy production. Microalgae biomass is considered as CO2 -neutral substitute for fossil fuel which results through net transfer of atmospheric CO2 into biomass. Traditionally, biofuel production process utilized lignocellulosic biomass as feedstock. Recently, microalgae rise as 3rd generation bioenergy feedstock due to its attractive higher CO2 fixation efficiency, higher biomass productivity and relatively easy pretreatment processes for various biofuel extractions. Although commercial microalgae CCS process is still at pilot scale and microalgae derived biofuels are nonviable. Further technological development in microalgae cultivation and bioenergy conversion enable the effective CO2 reduction and sustainable energy development simultaneously, and this review will update the progress in microalgae cultivation, biomass conversion to biofuel technology which can be utilized under BECCS technology. Highlights: BECCS technology with microalgae platform is promising for improved CO2 capture. It is an effective strategy to balance between carbon emission and removal. Flue gas can directly be used (with SOx and NOx) to microalgae cultivation. Microalgal BECCS technology attracts industries to reduce their carbon emissions. Microalgal biomass offer viable biofuels production process than other feedstock's.